2017
DOI: 10.3389/fpsyg.2017.01530
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Motor Learning Is More Pronounced in Proximal Compared to Distal Effectors in Upper Extremities

Abstract: The current experiment investigated generalizability of motor learning in proximal versus distal effectors in upper extremities. Twenty-eight participants were divided into three groups: training proximal effectors, training distal effectors, and no training control group (CG). Performance was tested pre- and post-training for specific learning and three learning transfer conditions: (1) bilateral learning transfer between homologous effectors, (2) lateral learning transfer between non-homologous effectors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 75 publications
5
30
0
Order By: Relevance
“…The role of acute exercise in promoting motor transfer has, by the authors' knowledge, rarely been examined in previous studies. Improved exercise-induced transfer, referring to the influence of previous practice on performing a skill in a new context [65], might occur through similar neuroendocrinological mechanisms as proposed for motor retention. In the current study, however, no such improved transfer was observed (see right-hand side, Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…The role of acute exercise in promoting motor transfer has, by the authors' knowledge, rarely been examined in previous studies. Improved exercise-induced transfer, referring to the influence of previous practice on performing a skill in a new context [65], might occur through similar neuroendocrinological mechanisms as proposed for motor retention. In the current study, however, no such improved transfer was observed (see right-hand side, Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…The analysis of the primary task used in the present study is the same analysis as we used in an earlier published study of learning transfer using proximal and distal joysticks (Aune et al, 2017). The dependent variable was measured as the average ASE in positioning of the crosshair relative to the target.…”
Section: Discussionmentioning
confidence: 99%
“…The sample comprised 14 university students with no known neuromuscular disorders or functional limitations (including normal and corrected vision) were recruited, seven women (mean age 23.9, SD = 7.5 years) and seven men (mean age 25.1, SD = 1.6 years). Based upon baseline (pre-test) proximaldistal differences in absolute spatial error (ASE) in a similar experimental task from a previous study (Aune et al, 2017), it was estimated that this sample size was sufficient to achieve a power of 80%, a level of significance of 5% (two sided) and effect size (Cohen's d) at 0.9, for detecting a mean proximaldistal differences in ASE that are significant different from zero (G * Power: Faul et al, 2007). All participants were right-handed as indicated by the Edinburgh Handedness Inventory (Oldfield, 1971) with a mean laterality index score of 0.94 (SD = 0.06).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…But with the engagement of additional DOFs-from the elbow and wrist-the control of fine motor skills becomes dominant in only one side (Newell & van Emmerik, 1989). This suggests that both the left and right-side shoulders are able to control one degree of freedom when the hand is in the maximum reachable amplitude, and thus facilitates learning transfer and generalisability (Aune et al, 2017).…”
Section: Introductionmentioning
confidence: 99%